Temporal Changes of Physical Parameters of Solid Waste During Barrel Composting - Hoque, MMM; Islam, S (Journal of Environmental Science and Natural Resources, 2019)
In this study solid waste were collected from 09 waste generating points of Mawlana Bhashani Science and Technology University during the study for composting. Volume reduction rate of solid waste was quick throughout 5-20 days and became slower during 25-35 days and finally became constant for last 10 days of observation, which indicated that quantity of nutrient materials for the bacterial growth became depleted and consequently the rate of decomposition of organic waste maybe slower at the last 10 days of observation. During the initial days, the increased temperature in the composting barrel was mainly caused by the more exothermic reactions associated with the respiratory metabolism of the microorganism involved in the composting of wastes. Volume reduction of organic wastes and the moisture contents shows similar trend. This result indicates that bacterial activities decrease with the reduction of moisture content of the wastes in the composting barrel. J. Environ. Sci. & Natural Resources, 11(1-2): 153-157 2018